Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702260
|View full text |Cite
|
Sign up to set email alerts
|

Problematising Upstream Technology through Speculative Design

Abstract: There is growing interest in technology that quantifies aspects of our lives. This paper draws on critical practice and speculative design to explore, question and problematise the ultimate consequences of such technology using the quantification of companion animals (pets) as a case study. We apply the concept of 'moving upstream' to study such technology and use a qualitative research approach in which both pet owners, and animal behavioural experts, were presented with, and asked to discuss, speculative des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…A more troubling matter, of which developers of T4As need be aware, is the potential impact of their intervention suggestions, and the extent to which they may override expert suggestions. A study by Lawson et al [31] showed that pet owners do not tend to question the outputs of the T4As, such as dog activity trackers, even valuing the output of the technology over the professional opinion of their veterinarian.…”
Section: Accuracy and Interpretability Of T4a-suggested Interventionsmentioning
confidence: 99%
“…A more troubling matter, of which developers of T4As need be aware, is the potential impact of their intervention suggestions, and the extent to which they may override expert suggestions. A study by Lawson et al [31] showed that pet owners do not tend to question the outputs of the T4As, such as dog activity trackers, even valuing the output of the technology over the professional opinion of their veterinarian.…”
Section: Accuracy and Interpretability Of T4a-suggested Interventionsmentioning
confidence: 99%
“…Ethical concerns and challenges of ACI were illustrated through examples of his research. One project applied speculative design to explore technologies for pet owners: several prototypes were developed and included tracking the animal's movement, a collar to interpret emotions, and a device to analyse cat excrement to identify health issues and track hunting behaviour [16]. This project emphasised the concern that technology industries push animal technology to unwary (human) consumers when this may be useless or even dangerous.…”
Section: Chronological Summarymentioning
confidence: 99%
“…3,7,9,17] The lighthearted aspects of the paper were, thankfully, acknowledged by the reviewers without detracting from the underlying serious rhetoric of the paper. The meta reviewer even points out that perhaps the main contribution goes beyond design fiction and into more fundamental discussions about research and HCI:…”
Section: This Was Indeed a Tricky Paper To Review It Is Very Well-wrmentioning
confidence: 99%